Indonesian Carbon Tax: How Newborn Learn to Jump into The Next Step? - Arief Budi Wardana; Mila Indriastuti; Dhian Adhetiya Safitra (Jurnal Akuntansi dan Keuangan, 2022)
As one of the largest emitting countries globally, Indonesia is a newcomer to carbon tax implementation. However, the carbon tax literature in Indonesian context is still minimal. This study aims to examine the implementation of carbon taxes in various countries, review the roadmap for implementing carbon taxes in Indonesia, and examine various mechanisms in other countries that have previously implemented carbon taxes by conducting literature review. The study results show that several countries have applied a broader carbon tax to several sectors and relatively higher tariffs than Indonesia. The long journey of the carbon tax before finally being scheduled on April 1, 2022, still needs to be improved in term of object, subject, reporting mechanism, and carbon tax rate. The author proposes the transportation sector as a complement to the coal power plant to change consumer behaviour towards products that produce carbon emissions.